2016
DOI: 10.1136/jnnp-2016-314704
|View full text |Cite
|
Sign up to set email alerts
|

Stroke paradox with SGLT-2 inhibitors: a play of chance or a viscosity-mediated reality?

Abstract: Diabetes mellitus is a major risk factor for cardiovascular morbidity and mortality. Current therapeutic strategies have not provided constant beneficial cardiovascular-related results. Sodium-glucose co-transporters 2 (SGLT-2) inhibitors have emerged as a novel antidiabetic class of drugs that exert favourable results in a variety of other cardiovascular risk factors too, such as increased blood pressure and body weight. The Empagliflozin, Cardiovascular Outcomes, and Mortality in Type 2 Diabetes (EMPA-REG OU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 46 publications
2
24
0
2
Order By: Relevance
“…This meta-analysis of 32 RCTs involving 75 540 participants from countries worldwide found that SGLT2 inhibitor treatment did not increase the risk of stroke, and there were no significant differences among drug classes, with either monotherapy or add-on combination therapy. Patient characteristics (gender, age, duration of DM, BMI and HbA1C levels) did not significantly affect stroke incidence, but African participants had a relatively lower incidence of stroke than We hypothesize that the mechanisms mediating the protective effects of SGLT2 inhibitors on CVD involve reductions in glucose, 15 Further studies are required to fully establish additional molecular mechanisms.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This meta-analysis of 32 RCTs involving 75 540 participants from countries worldwide found that SGLT2 inhibitor treatment did not increase the risk of stroke, and there were no significant differences among drug classes, with either monotherapy or add-on combination therapy. Patient characteristics (gender, age, duration of DM, BMI and HbA1C levels) did not significantly affect stroke incidence, but African participants had a relatively lower incidence of stroke than We hypothesize that the mechanisms mediating the protective effects of SGLT2 inhibitors on CVD involve reductions in glucose, 15 Further studies are required to fully establish additional molecular mechanisms.…”
Section: Discussionmentioning
confidence: 90%
“…Currently, there are insufficient data to determine whether the mild elevation of Hct, blood viscosity and LDL‐C overcome other stroke protection factors in patients receiving SGLT2 inhibitors. The apparently greater protection against cardiovascular death than against stroke suggests that other mechanisms may be involved, such as effects on atrial fibrillation and heart failure . Further studies are required to fully establish additional molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The interest on the association between hematocrit and stroke rekindled this year due to the divergent effect of a new class of antidiabetic drugs on cardiovascular mortality and stroke. 12 Indeed, sodium-glucose cotransporter-2 inhibitors were found to offer pronounced benefits on cardiovascular and all-cause mortality and heart failure protection; however, a disturbing and unexpected increased stroke risk was concomitantly reported. 13,14 The aim of this narrative review is to present existing data on the contribution of hematocrit in the development of stroke, and to attempt to unveil its relationship with the disease.…”
mentioning
confidence: 99%
“…Dle dat ze studie DECLARE-TIMI 58 se však nabízí použití inhibitorů SGLT2 i u pacientů bez prokázaného KVO v prevenci klinických událostí (hospitalizaci pro srdeční selhání) a pravděpodobně i progrese renálního onemocnění. Z předchozích studií s různými inhibitory SGLT2 vzešla nesourodá data o zvýšeném riziku ischemické CMP, amputacích a frakturách, 35,37,42,43 tyto nežádoucí události však nebyly ve studii DECLARE-TIMI 58 prokázány. Pozorován byl vyšší výskyt ketoacidózy, konzistentní s předchozími studiemi s inhibitory SGLT2.…”
Section: Glifl Ozinyunclassified